The Roles of Parents and Peer Friends on Adolescent Premarital Sex Behavior in High School Students of Buol District - Patui, Nurhaya S; Dasuki, Djaswadi; Wahyuni, Budi (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2018)
Background: Most adolescents or teens consider premarital sex behavior is a common and normal activity to do. Parents less able to communicate with their children will provoke conflicts in parents-children relationship and this may lead to impacts on premarital sex behavior in adolescents. Peer friends are also a source of information about sex that is quite significant in the shaping of adolescent knowledge, attitude and sexual behavior. However, information from peers may lead to negative impacts in adolescents such as premarital sex. This activity can lead to unwanted pregnancy, STIs, abortion and school dropouts.Objective: To determine the relationship between the roles of parents and peers in adolescent premarital sexual behavior in SMAN 1, SMA 2, SMK 1 and MAN in Buol.Methods: This study was observational with a cross-sectional design using quantitative and qualitative approaches. The study was held in SMAN 1, SMAN 2, SMK 1 and MAN of Buol District in Central Sulawesi with 192 adolescent as the research subjects. In-depth interviews were done to four selected informants.Result and Discussion: The results of bivariate analysis showed a significant relationship between the roles of parents and peers in adolescent premarital sexual behavior. Adolescents with low reproductive health information than that of parents have 2 times higher chance to perform high-risk sexual behaviors than adolescents with high reproductive health information than their parents. Adolescents with peers who give bad influence have a 5 times higher risk sexual behavior than teens with peers whose negative influence is lower. The results of this study also showed that there is a relationship between the influence of religiosity and pornographic media associated with high risk sexual behaviorConclusion: High-risk sexual behavior in adolescents is influenced by the parents’ role, poor informations on reproductive health high bad influence from peers is, low religiosity and exposure to pornographic media.Keywords: role of parents, peers, premarital sexual behavior